Renal Dysfunction and Mineral Metabolism Disturbances in Elderly Patients with COVID-19: A Controlled Clinical Study - Alaa Abed Faisal Faisal (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Coronavirus disease 2019 (COVID-19) is increasingly recognized as a multisystem disorder with notable renal and metabolic complications. Specific Background: While acute kidney injury during infection is well documented, persistent alterations in renal function and calcium–phosphate–vitamin D homeostasis after recovery, particularly in elderly individuals without comorbidities, remain insufficiently explored. Knowledge Gap: Limited case-control evidence exists integrating renal biomarkers and mineral metabolism parameters in older adults following SARS-CoV-2 recovery. Aims: This study aimed to assess long-term renal function and mineral metabolism disturbances and evaluate the diagnostic performance of related biomarkers in elderly men eight months post-COVID-19. Results: Compared to controls, post-COVID participants showed higher serum creatinine and blood urea and lower eGFR, alongside reduced serum calcium, inorganic phosphate, and 25-hydroxyvitamin D levels (p < 0.001). Individual biomarkers demonstrated strong discriminatory ability, while the combined multivariate model showed excellent discrimination, good calibration, and meaningful clinical utility. Renal indicators, particularly eGFR and blood urea, were the strongest predictors. Novelty: This study integrates renal and mineral biomarkers within an age-matched case-control framework, highlighting combined biomarker modeling for post-COVID assessment. Implications: Findings support sustained renal and metabolic monitoring in elderly populations after COVID-19 recovery and indicate the value of combined biomarker approaches for early detection of post-infectious renal involvement. Highlights:• Persistent kidney filtration abnormalities observed eight months after recovery• Marked disruption in calcium, phosphate, and vitamin D balance detected• Combined biomarker model shows strong diagnostic discrimination and clinical utility Keywords: COVID-19, Renal Dysfunction, Mineral Metabolism, eGFR, Vitamin D